(untitled) (LEARNing Landscapes, 2019)
In this interview with author and educator Nick Sousanis, he discusses his PhD dissertation, which was written and drawn entirely in comic book form and later published by Harvard University Press under the title “Unflattening.” He describes how he proceeded with the idea of producing a dissertation in comic form and the support he received from his professors. He strongly believes that it is possible to convey complex ideas in comic form and that the form itself draws people in. He also shares what he learns from his students—often non-drawers—and gives examples of innovative work produced by them.